Soft Computing Control System of an Unmanned Airship - Kitt, Wong Wei; Chekima, Ali; Dhargam, Jamal A.; Wong, Farrah; A.Tabet, Tamer (Iraqi Journal for Electrical and Electronic Engineering, 2010)
Soft computing control system have been applied in various applications particularly in the fields of robotics controls. The advantage of having a soft computing controls methods is that it enable more flexibility to the control system compared with conventional model based controls system. In this paper, a UAV airship is controlled using fuzzy logic for its propulsion and steering system. The airship is tested on a simulation level before test flight. The prototype airship has on board GPS and compass for telemetry and transmitted to the ground control system via a wireless link.